2007
DOI: 10.1136/bjo.2007.122572
|View full text |Cite
|
Sign up to set email alerts
|

Degree of angle closure and extent of peripheral anterior synechiae: an anterior segment OCT study

Abstract: Angle width determined by AS-OCT and the extent of PAS were weakly correlated, and angle width was significantly smaller in eyes with PAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 13 publications
0
36
0
Order By: Relevance
“…Su et al demonstrated a correlation between anterior chamber angle width and the degree of PAS, with the narrowest angles demonstrating the highest clock hours of PAS. 37 In a 3 year follow up period, one out of three eyes of patients with PAS who received LPI experienced PAS extension. 38 LPI can effectively treat eyes with angle closure when the only underlying mechanism is pupillary block, but tends to be less effective in eyes with PAS.…”
Section: Discussionmentioning
confidence: 98%
“…Su et al demonstrated a correlation between anterior chamber angle width and the degree of PAS, with the narrowest angles demonstrating the highest clock hours of PAS. 37 In a 3 year follow up period, one out of three eyes of patients with PAS who received LPI experienced PAS extension. 38 LPI can effectively treat eyes with angle closure when the only underlying mechanism is pupillary block, but tends to be less effective in eyes with PAS.…”
Section: Discussionmentioning
confidence: 98%
“…Informed consent was obtained from all participants, and the study, which adhered to the tenets of the Declaration of Helsinki, had the approval of the Singapore Eye Research Institute Review Board. The details of AS-OCT imaging technology have been described previously 4. Briefly, the image is horizontally composed of 256 A-scans in 16 mm with 1024 points per A-scan in 8 mm of depth.…”
Section: Methodsmentioning
confidence: 99%
“…Its performance has been described. 9 The system uses a 1310 nm superluminescent diode source and operates up to a speed of 8 frames per second (2000 A-scans per second). The transverse resolution is 60 mm and the axial resolution, 10 to 20 mm.…”
Section: Optical Coherence Tomography Systemsmentioning
confidence: 99%